IMPLEMENTASI KEBIJAKAN NOMOR 19 TAHUN 2009 TENTANG PENGENDALIAN MUTU AUDIT PADA INSPEKTORAT KABUPATEN WAY KANAN - ida farida; Malik Malik (Universitas Bandar Lampung (UBL), 2020)
The problem in this research is (1) how policy implementation No. 19 of 2009 about quality control guidelines Audit on the Inspectorate of Right Way District, (2) What aspects inhibit policy implementation number 19 year 2009 Audit quality control Guidelines on the Inspectorate of the right Way district. This method of research is using a qualitative research type with a descriptive analysis method. The use of this method is to examine and describe qualitatively, how the implementation of policy No. 19 of 2009 on quality control guidelines for Audit on the Inspectorate of Way Kanan District. The results showed that the implementation of policy No. 19 of 2009 on the Audit quality control guidelines on the Inspectorate of Way Kanan District, has been running by utilizing the human resources potential, according to the concept (1) communication, Implementation of policy No. 19 year 2009 is always communicated to the target institution, (2) the disposition/attitude of the officer, in general the employee has been good according to the provisions in carrying out the task, (3) resources, standards of Human resources competency The inspectorate has not been fulfilled, so the audit results are relatively less than optimal (4) bureaucratic structure, it has to do the task and authority is at the leadership of the organization that distributes tasks to subordinates. Aspects that inhibit policy implementation No. 19 year 2009 about quality control Audit at the Inspectorate of the right Way, (1) The unit of results, the result of the monitoring of the aforementioned Bulum is fully acted upon on the Findings by OPD; So that the results of the audit is relatively less than optimal, (2) The unit time inspection is not uniform, so the timeliness in can impede the smooth audit quality, (3) The quality of work, with the weak audit techniques to uncover The substance of the findings is still weak, the results of work done relatively not optimal.